2020
DOI: 10.1089/bio.2020.0048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microwave-Assisted Drying on Structural Integrity and Viability of Testicular Tissues from Adult and Prepubertal Domestic Cats

Abstract: Anhydrous preservation is a promising approach for storage of living biomaterials at nonfreezing temperatures. Using the domestic cat model, the objectives of this study were to characterize changes in histology, DNA integrity, and viability of testicular tissues from adult versus prepubertal individuals during microwave-assisted drying. Testes from each age group were cut into small pieces before reversible membrane permeabilization, exposure to trehalose, and microwave-assisted drying during different time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Mature testicular tissue from adult cats also was more responsive transcriptionally to vitrification compared to juvenile. Similarly, immature testes from domestic cat were reported to be more resilient to microwave-assisted dehydration [ 25 ] and more successful in surviving and establishing spermatogenesis in xenografts [ 51 , 52 ], compared to mature testes from adult cats. Specifically, we observed the downregulation of functional terms related to focal and cell-cell adhesion in adult compared to late juvenile, as well as to the whole juvenile group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mature testicular tissue from adult cats also was more responsive transcriptionally to vitrification compared to juvenile. Similarly, immature testes from domestic cat were reported to be more resilient to microwave-assisted dehydration [ 25 ] and more successful in surviving and establishing spermatogenesis in xenografts [ 51 , 52 ], compared to mature testes from adult cats. Specifically, we observed the downregulation of functional terms related to focal and cell-cell adhesion in adult compared to late juvenile, as well as to the whole juvenile group.…”
Section: Discussionmentioning
confidence: 99%
“…DNA integrity was assessed using the protocol reported previously for domestic cat testicular tissue using the In-Situ Cell Death Detection kit (Roche, Basel, Switzerland) [ 25 ]. Deparaffinized rehydrated sections were rinsed twice with 0.05 % Triton X-100 in PBS for 5 min each, permeabilized with 0.5 % Triton X-100 in PBS for 30 min, rinsed once with 0.05 % Triton X-100 in PBS for 5 min and incubated in TUNEL reaction mixture (enzyme solution with terminal deoxynucleotidyl transferase (TdT) and label solution with nucleotide polymers) for 1 h at 37 °C within a humidified darkened container.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Present results were obtained in adult tissues, but it is expected that structural or functional properties in testes from prepubertal or younger BFFs would be comparable or even better, as seen in the preservation of cat testicular tissues [15]. Collective results helped to better characterize the resilience of BFF testicular tissues to freezing temperatures and the essential role of rapid warming followed by a 24-h reanimation period.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies reported that germ cells at the early stages of spermatogenesis are more sensitive to DNA damage than sperm cells. Non-physiological conditions created by the preservation methods break hydrogen bonds between the bases of the DNA strands [15]. Our next step is to decipher and quantify DNA repair mechanisms in tissues through staining of proliferating cell nuclear antigen (PCNA) or RAD51 protein [16] and detection of heat shock proteins [17].…”
Section: Discussionmentioning
confidence: 99%